Sodium Glucose Cotransporter-2 Inhibitors Improve Endothelial Function and Arterial Stiffness in Diabetic Individuals: A Systematic Review and Network Meta-Analysis - Sridharan, Kannan; Sivaramakrishnan, Gowri (Current Vascular Pharmacology, 2025)
IntroductionSodium Glucose cotransporter-2 inhibitors (SGLT2is) possess pleiotropic effects, such as antioxidant, antifibrotic, anti-inflammatory, and vascular remodeling activities. Considering the lack of literature, a network meta-analysis was conducted to explore the impact of SGLT2is on endothelial dysfunction and arterial stiffness in the diabetic population.MethodsElectronic databases were searched to identify randomized clinical trials evaluating the effects of SGLT2is on outcomes, such as Flow-mediated Vasodilation (FMV), Pulse Wave Velocity (PWV), and Augmentation Index (AIx). Direct, indirect, and mixed treatment comparisons generated pooled estimates using random-effects modeling. Effect sizes were reported as Hedges' g with 95% Confidence Interval (95% CI). Bootstrap and permutation meta-analyses were performed using ranking plots. The certainty of evidence was graded.ResultsTwelve articles (706 participants) were included. SGLT2is were associated with significant improvements in FMV (g: 0.48; 95% CI: 0.08, 0.88), confirmed by bootstrap meta-analysis (g: 0.48; 95% CI: 0.1, 0.85) and permutation meta-analysis of FMV (g: 0.48; 95% CI: 0.05, 0.9). Within SGLT2is, dapagliflozin (g: 0.39; 95% CI: 0.14, 0.65) significantly improved FMV, and dapagliflozin (g: -0.61, 95% CI: -0.98, -0.24) and tofogliflozin (g: -3.51; 95% CI: -4.05, -2.98) significantly improved PWV. A low risk of publication bias was observed, and the ranking plots revealed dapagliflozin to have the best probability (0.99) of being the most effective for improving FMV. Low certainty of evidence was observed for all outcomes.ConclusionSGLT2 inhibitors improve endothelial function and arterial stiffness in the diabetic population. Clinical studies evaluating the association between improvements in endothelial function with SGLT2is and reduced adverse cardiovascular and cardiorenal events and mortality are urgently needed.
Keywords: tofogliflozin